Enhancing Smart Irrigation With Centralized Data - Guzmán, Sandra M. (EDIS, 2024)
In the context of modern agriculture, efficient irrigation management plays a crucial role in optimizing tree growth and promoting sustainable management practices. This article introduces IrrigMonitor, an Internet of Things (IoT) data visualization platform developed at the UF Indian River Research and Education Center (IRREC) Smart Irrigation and Hydrology lab. IrrigMonitor is a centralized system that offers real-time insights into soil moisture levels and allows for customized adjustments based on specific soil conditions. This article presents an overview of IrrigMonitor's interface, explores its functionality, and discusses its potential applications in citrus water and nutrient management.